Punitive ambiguity: State-level criminal record data quality in the era of widespread background screening - McElhattan, David (Punishment & society, 2022)
Prior research documents widespread deficiencies in the quality and completeness of official criminal records in the United States. In an era when the social reach of criminal records has expanded to an unprecedented degree, these deficiencies carry serious consequences for criminal record subjects. The present study develops the concept of punitive ambiguity to characterize the burdens of incomplete criminal records and examines how they vary at the state level, providing evidence that punitive ambiguity is racially patterned. Using data from the biennial Surveys of State Criminal History Information Systems, multivariate analyses find that states where African Americans make up larger shares of felony record populations report rap sheet dispositions at significantly lower levels, pairing low criminal record data quality with extensive legally-mandated background screening. The results carry implications for understanding the racialized burdens of a criminal record, as well as broader processes in the development of the American penal state that combine harsh formal punishments with chronic administrative neglect.